Association between polymorphisms in MRE11 and HIV-1 susceptibility and AIDS progression in a northern Chinese MSM population. (15th April 2019) - Liu, Chang; Qiao, Yuandong; Xu, Lidan; Wu, Jiawei; Mei, Qingbu; Zhang, Xuelong; Wang, Kaili; Li, Qiuyan; Jia, Xueyuan; Sun, Haiming; Wu, Jie; Sun, Wenjing; et al.
Abstract: Background: Previous studies reported that DNA damage repair (DDR) genes may play an important role in HIV-1 infection. The MRE11 gene, a member of the MRN complex, plays an essential part in the homologous recombination pathway, which is one of the classical DDR pathways. Previous reports have demonstrated that MRE11 has an effect on HIV-1 replication. However, the role of SNPs in the MRE11 gene and their impact on HIV-1 infection and AIDS progression remain unknown. Methods: In this study, 434 MSM HIV-1-infected patients in northern China and 431 age-matched healthy controls were enrolled. Five SNPs (rs2155209, rs10831234, rs13447720, rs601341 and rs11020803) at the MRE11 gene were genotyped. Another series of cases (409 MSM HIV-1-infected patients) and controls (403 age-matched healthy males) were recruited as the validation set. Results: In our study, rs10831234 showed differences in allele frequencies between cases and controls ( P = 0.005). Additionally, there was an association between rs10831234 and HIV-1 infection susceptibility in dominant and additive models ( P = 0.005 and P = 0.006, respectively). All significant associations were replicated in the validation set, and the associations were still significant after Bonferroni correction for multiple testing when the two data sets were combined. Furthermore, in haplotype association analyses between the case and control groups, the frequencies of the haplotypes Crs11020803 Crs10831234 and Trs11020803 Trs10831234 showed significant differences ( P = 0.0181 and P = 0.0068, respectively). Conclusions: We demonstrated that the MRE11 rs10831234-T allele may confer increased risk of HIV-1 infection.